If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 17x + -3(4 + 5x) = 44 17x + (4 * -3 + 5x * -3) = 44 17x + (-12 + -15x) = 44 Reorder the terms: -12 + 17x + -15x = 44 Combine like terms: 17x + -15x = 2x -12 + 2x = 44 Solving -12 + 2x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = 44 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 44 + 12 2x = 44 + 12 Combine like terms: 44 + 12 = 56 2x = 56 Divide each side by '2'. x = 28 Simplifying x = 28

| -17=b+4 | | -90+2y=10-3y | | 4x+y=-7 | | 6(z-1.8)=9.3 | | -12n-3=45 | | y-3=2x | | -6(n+-12)=48 | | 35-5(2x+3)=20 | | 3x-y=-2 | | y+7=5x | | 6x+3y=12 | | s+(-9)=7 | | y=x-2 | | 3x-y=1 | | -77=-7(k+3) | | k+89.2=47.62 | | 5+3x=x+25 | | 8(3x-5)+20=-68 | | 4(3x+2)-18=14 | | 5x-3y=19 | | 5y-0.6=0.8 | | -30n=-27n-36 | | 17-(6x+3)=-16 | | (x)(x+4)=32 | | 35y^2-15y=5y | | 7x+2y=8 | | x+2+10+x^2=0 | | cz+c^2=5c^2-3cx | | 19+h=-4 | | 3(u-3)=4(u+3) | | 8x^2=18x-10 | | X+9=6x-31 | | 7x+4x+2+5=6x+3+4x | | bx-5=c | | 8x-3=7x+2 | | 14x^2-39xy-35y^2= | | y=5x-25 | | -3(3b+3)+(10b-7)=0 | | -14=6-4x | | 9+2x=3x+5 | | 2x^2-7x-70=-3x | | 8-3x=-13 | | 30w+72=-3w^2 | | 3x-(2x+5)=-3 | | -x^2+16x+17=0 | | 6x^2=10x-4 | | -2+16=0 | | 4x-9=-1 | | c^2=144 | | (x-6)(x-4)=8 | | 5m-18=6m+4 | | 2(a^2+10)=13a | | 8(a+10)= | | 4-6x=50 | | 26n+15=32n+3 | | -12h+39=4n-17 | | 16b-4=38b+84 | | -(x-4)=19X+8 | | 5(z+6)=8z | | 7(7-3u)=-u-11 | | -(x^2)-x-30=(2x^2)-9x+4 | | -3(x+5)=2(x+5) | | s^4-15=9 | | -4(3x+2)=3(6x-6) | | 6x-9x-4=2y-2 |